Clinical practice guidelines for the care and treatment of breast cancer: 15. Treatment for women with stage III or locally advanced breast cancer - Shenkier, Tamara (Canadian Medical Association, 2004)
OBJECTIVE: To define the optimal treatment for women with stage III or locally advanced breast cancer (LABC). EVIDENCE: Systematic review of English-language literature retrieved from MEDLINE (1984 to June 2002) and CANCERLIT (1983 to June 2002). A nonsystematic review of the literature was continued through December 2003. RECOMMENDATIONS: · The management of LABC requires a combined modality treatment approach involving surgery, radiotherapy and systemic therapy. Systemic therapy: chemotherapy Operable tumours · Patients with operable stage IIIA disease should be offered chemotherapy. They should receive adjuvant chemotherapy following surgery, or primary chemotherapy followed by locoregional management. · Chemotherapy should contain an anthracycline. Acceptable regimens are 6 cycles of FAC, CAF, CEF or FEC. Taxanes are under intense investigation. Inoperable tumours · Patients with stage IIIB or IIIC disease, including those with inflammatory breast cancer and those with isolated ipsilateral internal mammary or supraclavicular lymph-node involvement, should be treated with primary anthracycline-based chemotherapy. · Acceptable chemotherapy regimens are FAC, CAF, CEF or FEC. Taxanes are under intense investigation. · Patients with stage IIIB or IIIC disease who respond to primary chemotherapy should be treated until the response plateaus or to a maximum of 6 cycles (minimum 4 cycles). Patients with stage IIIB disease should then undergo definitive surgery and irradiation. The locoregional management of patients with stage IIIC disease who respond to chemotherapy should be individualized. In patients with stage IIIB or IIIC disease who achieve maximum response with fewer than 6 cycles, further adjuvant chemotherapy can be given following surgery and irradiation. Patients whose tumours do not respond to primary chemotherapy can be treated with taxane chemotherapy or can proceed directly to irradiation followed by modified radical mastectomy, if feasible. Systemic therapy: hormonal therapy Operable and inoperable tumours · Tamoxifen for 5 years should be recommended to pre- and postmenopausal women whose tumours are hormone responsive. Locoregional management Operable tumours · Patients with stage IIIA disease should receive both modified radical mastectomy (MRM) and locoregional radiotherapy if feasible. They may be managed with MRM followed by chemotherapy and locoregional radiotherapy, or chemotherapy first followed by MRM and locoregional radiotherapy. Breast-conserving surgery is currently not a standard approach. · Locoregional radiotherapy should be delivered to the chest wall and to the supraclavicular and axillary nodes. The role of internal mammary irradiation is unclear. Inoperable tumours · Patients with stage IIIB disease who respond to chemotherapy should receive surgery plus locoregional radiotherapy. · The locoregional management of patients with stage IIIC disease who respond to chemotherapy is unclear and should be individualized. · Patients whose disease remains inoperable following chemotherapy should receive locoregional radiotherapy with subsequent surgery, if feasible. VALIDATION: The authors' original text was revised by members of the Steering Committee on Clinical Practice Guidelines for the Care and Treatment of Breast Cancer. Subsequently, feedback was provided by 9 oncologists from across Canada. The final document was approved by the steering committee. SPONSOR: The Steering Committee on Clinical Practice Guidelines for the Care and Treatment of Breast Cancer was convened by Health Canada. COMPLETION DATE: December 2003.